TSH Receptor Antibody and its Importance in Treatment of Hyperthyroidism - Mall, Dipak; Thapaliya, S (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Thyrotoxicosis has multiple etiologies, manifestations, and potential therapies. Appropriate treatment requires an accurate diagnosis and is influenced by coexisting medical conditions and patient preference. Biochemical value of TSH Receptor Antibody plays a vital role in diagnosis of Graves’s disease from Thyroiditis. This helps us to avoid unnecessary treatment of hyperthyroidism with anti thyroidal drugs. Method: This is a cross-sectional Study done in the patients with biochemical lab reports of hyperthyroidism. TSH Receptor antibody lab test was done in various labs in Kathmandu as per patient’s choice. TSH receptor antibody was defined as positive and negative as per results above 1.8 IU/L and below 1.8 IU/L respectively. Results above 1.8 were treated accordingly as per standard protocol and available treatment options in National Academy of Medical sciences. Results: 153 Patients were evaluated for TSH receptor antibody test.109 female and 54 males. Among female 27 and 82 were found to have below 1.8 IU/L and above 1.8 IU/L respectively. And in males 23 and 18 were below 1.8 IU/L and above 1.8 IU/L respectively. The youngest male was of age 17 year with TSH receptor antibody below 1.8 IU/L and oldest male was of age 58 year with TSH receptor antibody below 1.8 IU/L. The youngest female was of age 17 year with TSH receptor antibody below 1.8 IU/L and oldest female was of age 72 year with TSH receptor antibody above 1.8 IU/L. In both male and female, the maximum number of patients visiting our center was average age of 31-40 years of age. Conclusion: TSH receptor Antibody laboratory is now easily available in Kathmandu valley, though it is now done in National academy of medical sciences. I have found it very easy to access the patients presenting with biochemical reports of hyperthyroidism and further plan for treatment as per reports of TSH receptor Antibody. Biochemical value of TSH Receptor Antibody plays a vital role in diagnosis of Graves’ disease from Thyroiditis. This helps us to avoid unnecessary treatment of hyperthyroidism with Anti thyroidal drugs.